Construct validity of questionnaires for the original and revised reinforcement sensitivity theory - Leue, Anja; Reuter, Martin; Corr, Philip J.; Ettinger, Ulrich (Frontiers in Psychology, 2022)
This study highlights psychometric properties and evidence of construct validity on parcel-level for questionnaires on the original and revised reinforcement sensitivity theory. Our data (N = 1,076) suggest good to very good psychometric properties and moderate to excellent internal consistencies. CFA models suggest a very good model fit for the first-order, four factor models of the Carver-White BIS/BAS scales, Reinforcement Sensitivity Theory - Personality Questionnaire (RST-PQ), the two-factor model of revised Reinforcement Sensitivity Theory -Questionnaire (rRST-Q) and for the bifactor model of the Conflict Monitoring Questionnaire (CMQ-44). The CMQ-44 extends the psychometric measurement of previous trait-(r)BIS and trait-BAS scales. Factor scores of CMQ-44 cognitive demand correlate positively with factor scores of Carver-White BIS and all Carver-White BAS subfactors except RST-PQ-Impulsivity suggesting that CMQ-44 cognitive demand addresses Carver-White trait-BIS specifically and more generally the trait-BAS core. CMQ-44 anticipation of negative consequences and response adaptation correlate negatively with trait-BAS, whereas the second-order factor performance monitoring extends the (r)RST trait-space and correlates positively with trait-BAS.